2017
DOI: 10.1039/c7cc01286a
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of minor actinides, lanthanides and other fission products by silica-immobilized BTBP/BTPhen ligands

Abstract: Novel BTBP [bis-(1,2,4-triazin-3-yl)-2,2'-bipyridine]/BTPhen [bis-(1,2,4-triazin-3-yl)-1,10-phenanthroline] functionalized silica gels have been developed to extract minor actinides, lanthanides and other fission products. BTPhen functionalized silica gel is capable of near-quantitative removal of Am(iii) in the presence of Eu(iii) from aqueous HNO, while BTBP functionalized silica gel is able to remove problematic corrosion and fission products that are found in PUREX raffinates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…Immobilization of (4-hydroxyphenyl) functionalized CyMe4-BTPhen 6 on silica gel previously observed for 4 and 5 and may, to some extent, be attributed to the increased degree of ligand protonation and thus decreased free ligand concentration. 29,30 The effect of HNO3 concentration on the degree of extraction of Am(III) and Eu(III) also mirrors that of 4 and 5, where it was concluded that the limited length of the linking-chain on the MNP/silica gel forced the quadridentate BTPhen ligand to form a 1:1 complex with 10-coordinate M(III) cations. 29,30 Thus, whilst the decreasing pH affected the extraction of both Am(III) and Eu(III), we were intrigued by the possibility that it might be the nature of the counterion surrounding the M(III) species in the 1:1 complex that was leading to the increasing distinction between Am(III) from Eu(III) at increasing HNO3 concentration.…”
mentioning
confidence: 77%
See 3 more Smart Citations
“…Immobilization of (4-hydroxyphenyl) functionalized CyMe4-BTPhen 6 on silica gel previously observed for 4 and 5 and may, to some extent, be attributed to the increased degree of ligand protonation and thus decreased free ligand concentration. 29,30 The effect of HNO3 concentration on the degree of extraction of Am(III) and Eu(III) also mirrors that of 4 and 5, where it was concluded that the limited length of the linking-chain on the MNP/silica gel forced the quadridentate BTPhen ligand to form a 1:1 complex with 10-coordinate M(III) cations. 29,30 Thus, whilst the decreasing pH affected the extraction of both Am(III) and Eu(III), we were intrigued by the possibility that it might be the nature of the counterion surrounding the M(III) species in the 1:1 complex that was leading to the increasing distinction between Am(III) from Eu(III) at increasing HNO3 concentration.…”
mentioning
confidence: 77%
“…[23][24][25][26][27][28] We have recently developed and reported magnetic nanoparticle (MNP) and silica gel-based solid phase extractants ( Figure. 2), where we have demonstrated that immobilized BTPhen type ligands could be used either to extract both An(III) and Ln(III) at low concentrations of HNO3 or to extract An(III) selectively over Ln(III) at high concentrations of HNO3. 29,30 Previously, we reported a partitioning process for minor actinides and lanthanides based on a column separation technique using the novel tetra(4-hydroxyphenyl)-BTPhen-functionalized SiO2 gel 5. 29 Herein, we report the synthesis and extraction properties of a new CyMe4-BTPhen-functionalized SiO2 gel 8 and investigations into the nature of the counterion influence on extraction efficiency.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In conventional solvent extraction, 2,6-bis(5,6-dialkyl-1,2,4-triazin-3-yl)pyridines (BTPs) [6], 2,9-bis(1,2,4triazin-3-yl)-1,10-phenanthroline (BTPhens) [7] or N,N,N',N'-tetrakis(2-pyridylmethyl) ethylenediamine (TPEN) [8] etc. have been widely studied.…”
Section: Introductionmentioning
confidence: 99%